A qualitative analysis of factors that influence Vietnamese ethnic minority women to seek maternal health care - Shannon McKinn; Duong Thuy Linh; Kirsty Foster; Kirsten McCaffery (BMC Pregnancy and Childbirth, 2019)
Abstract Background Dien Bien Province in northwest Vietnam is predominantly populated with ethnic minority groups, who experience worse maternal and child health outcomes than the general population. Various factors are associated with maternal health care utilisation in Vietnam, including ethnic minority status, which is recognised as a key determinant of inequity in health outcomes. The aim of this study is to explore how and why ethnic minority women utilise maternal health services, and the factors that influence women and families’ decisions to access or not access facility-based care. Methods We used a qualitative approach, interviewing primary health care professionals (n = 22) and key informants (n = 2), and conducting focus groups with Thai and Hmong women (n = 42). A thematic analysis was performed. Results There were three main themes. 1. Prioritising treatment over prevention: women talked about accessing health services for health problems, such as unusual signs or symptoms during pregnancy, and often saw limited utility in accessing services when they felt well, or for a normal physiological event such as childbirth. Health professionals also saw their role as being mainly treatment-oriented, rather than prevention-focused. 2. Modernisation of traditional practices: health professionals and ethnic minority women discussed recent improvements in infrastructure, services, and economic circumstances that had increased access to health services. However, these improvements were less pronounced in Hmong communities, suggesting inequity. 3. Perceptions of quality influenced service utilisation: both health professionals and ethnic minority women perceived primary care facilities to be of lower quality compared to hospital, and some women made decisions about accessing services based on these perceptions, preferring to travel further and spend more to access higher quality services. Health professionals’ perceptions of low service quality appeared to influence their referral practices, with even uncomplicated cases referred to higher level services as a matter of course. Conclusions Primary health care facilities were technically available and accessible to ethnic minority women, however these services were likely to be underutilised if they were perceived to be of low quality. Some women had the means to access higher quality facilities, but others were limited to lower quality facilities, potentially reinforcing inequities in health outcomes.